Morphometric Indicators of Head Parameters in Girls With Hearing Loss (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The morphometric parameters of the head of girls with hearing loss from birth to 12 years old were measured, analyzed and compared. It can be seen that with the growing age of the child, some morphometric indicators of the head grow at the same rate in different age periods of childhood, but the intensity of the growth rate of some indicators is not the same in the age periods of childhood.